Vascular Reactivity Concerning Orthosiphon stamineus Benth-Mediated Antihypertensive in Aortic Rings of Spontaneously Hypertensive Rats. (26th June 2013) - Manshor, Nurul Maizan; Dewa, Aidiahmad; Asmawi, Mohd Zaini; Ismail, Zhari; Razali, Nadiah; Hassan, Zurina
Abstract : Orthosiphon stamineus Benth has been traditionally used to treat hypertension. The study aimed to investigate the vascular reactivity of water extract (WOS) and water : methanolic (1 : 1) extract (WMOS) of Orthosiphon stamineus Benth and AT1 receptors blocker in the mechanisms of antihypertensive mediated by α 1 -adrenergic receptor and EDNO and PGI2 releases in the SHR aortic rings. SHR (230–280 g) were divided into four groups: control, WOS, WMOS, and losartan. After being fed orally for 14 days, the aorta was harvested and subjected to PE (10 −9 to 10 −5  M) and ACh (10 −9 to 10 −5  M) with and without L-NAME (100 µM) and indomethacin (10 µM), respectively. WOS, WMOS, and losartan significantly reduced the contractile responses to PE intact suggesting the importance of endothelium in vasorelaxation. Losartan significantly enhanced the ACh-induced vasorelaxation. L-NAME significantly inhibited the ACh-induced relaxation in all groups. Indomethacin enhanced ACh-induced vasorelaxation in WMOS. Collectively, Orthosiphon stamineus leaves extract reduced vasoconstriction responses by the alteration of α 1 -adrenergic and AT1 receptors activities. The involvement of EDNO releases was clearly observed in this plant. In WOS, PGI2 releases might not participate in the ACh-induced vasorelaxation. However, in WMOS, enhancement of vasorelaxation possibly due to continuous release of PGI2 .